Radiation decreases bronchial epithelial progenitor function as assessed by organoid formation - Merian E. Kuipers; Dennis K. Ninaber; Krista C.J. van Doorn-Wink; Annelies M. Slats; Pieter S. Hiemstra (Respiratory Research)
Abstract Objective Radiation-induced lung injury (RILI) is a serious side-effect of radiotherapy for lung cancer, in which effects on the normal lung epithelium may play a key role. Since these effects are incompletely understood, the aim of the present study was to evaluate the effect of ionizing radiation (IR) on cultured well-differentiated primary bronchial epithelial cells (PBEC) with a focus on cytotoxicity, barrier formation, inflammation and epithelial progenitor function. Materials and methods PBEC were cultured at the Air-Liquid Interface (ALI-PBEC) to allow mucociliary differentiation. Effect of IR (1, 2, 4, 8 Gy [Gy]) on ALI-PBEC cultures was investigated by lactate dehydrogenase (LDH) release, Trans Epithelial Electrical Resistance (TEER; as a measure of barrier function), qPCR (P21/CDKNA1, MKI67, AEN, E2F1, ATF3) and immunofluorescence staining (γH2Ax-foci). The impact on epithelial progenitor function was assessed by studying organoid formation capacity of irradiated ALI-PBEC at 24 h and 7 days after IR. Results and discussion IR increased the number of γH2Ax-foci (marker of double stranded DNA breaks) in ALI-PBEC, but did not affect markers of toxicity (LDH-release or TEER). IR did also not affect mRNA markers for inflammation or epithelial-mesenchymal transition (EMT), but did increase mRNA levels of the cell cycle inhibitor P21/CDKN1A and resulted in downregulation of the proliferation markers MKI67 and E2F1. Finally, IR of ALI-PBEC had a marked effect on organoid formation capacity, which was markedly impaired following IR in a dose-dependent manner. Conclusion In conclusion, epithelial progenitor cell function as assessed by organoid formation capacity is strongly reduced by IR and persists for at least 7 days. Despite an effect on organoid formation capacity, DNA breaks, P21/CDKN1A expression and reduced expression of MKI67 and E2F1, this effect was not accompanied by IR-induced cytotoxicity, or an increase in markers of inflammation or EMT. This study indicates that studying the effects of IR on organoid formation is a valid and sensitive tool to study adverse effects of IR on normal lung epithelial cells and could be used as a tool to study RILI.